A study of treatment preference for diarrhea among Tengger people in Pasuruan, East Java, Indonesia. Issue 3 (23rd September 2020) - Pratama, Antonius Nugraha Widhi; Ningsih, Lutfia Wildatul Cahya; Rachmawati, Ema; Triatmoko, Bawon; Tan, Elizabeth Yu; Nugraha, Ari Satia
Abstract : Purpose: This study aims to describe the treatment preference, especially in relation to traditional medicine, modern health care and a combination of both, in diarrheal cases among the Tengger ethnic minority group. Design/methodology/approach: A cross-sectional survey was conducted in all eight villages of Tosari District, Pasuruan Regency, East Java Province. Tengger people were major resident in the area for generations. Convenience sampling and a face-validated structured questionnaire were used to recruit and face-to-face interview 377 Tengger people. Findings: The study found that modern health care was the dominant preference (52%, n  = 196) selected by Tengger people when they have an episode of diarrhea, compared to traditional medicines and mixed approach. Most respondents opted to visit one facility or to stay at home (64.3%, n  = 242). Statistical significant relationships were found between treatment choice and age ( p  < 0.001), sex ( p  < 0.001), religion ( p  = 0.011), distance ( p  < 0.001), educational background ( p  < 0.001) and job ( p  < 0.001). A clear pattern between treatment choice and age was revealed with younger groups tended to choose modern health care, while older groups more preferred the traditional approach. Practical implications: This work could provide an insight that when the young Tengger people are having uncomplicated and common health illness, such as diarrhea, they tend to use modern treatment approach. Originality/value: This study fulfilled an identified need to explore the trend of treatment approach across generations in the Tengger society as a model of the minor ethnic group in Indonesia.